Asymptomatic carotid artery stenosis and retinal nerve fiber layer thickness: a community-based, observational study - Wang, Dandan; Jonas, Jost B. (PLOS ONE, 2017)
Purpose To examine whether an abnormally thin retinal nerve fiber layer (RNFL) is associated with cerebrovascular insufficiency. Design Community-based study. Methods The Asymptomatic Polyvascular Abnormalities in Community Study included Chinese aged 40+ years and without histories of cerebrovascular incidents or coronary heart disease. Using transcranial Doppler and carotid duplex ultrasound examination, we assessed presence and degree of an intracranial arterial stenosis (ICAS) and extracranial carotid arterial stenosis (ECAS) and we measured the RNFL thickness by spectral-domain optical coherence tomography. Results The study included 3,376 participants with a mean age of 54.3±10.3 years. Thinner RNFL was significantly correlated with a higher prevalence of ECAS (P = 0.035; standardized regression coefficient beta:-0.04; non-standardized regression coefficient B:-0.99; 95% confidence intervals(CI):-1.90,-0.07), after adjusting for age (P<0.001;beta:-0.25;B:-0.26;95%CI:-0.30,-0.22), gender (P = 0.001;beta:-0.07;B:-1.36;95%CI:-2.14,-0.58) and blood concentration of low-density lipoproteins (P = 0.03;beta:0.04;B:0.52;95%CI:0.05,0.98). In a reverse manner, prevalence of ECAS was associated with a thinner RNFL thickness (P = 0.007; odds ratio (OR):0.99; 95%CI:0.98,0.99) after adjusting for older age (P<0.001;OR:1.06;95%CI:10.05,10.7), higher prevalence of ICAS (P = 0.01;OR:1.34;95%CI:1.07,1.69) and higher prevalence of carotid artery plaques (P<0.001;OR:9.18;95%CI:6.93,12.2), and higher blood concentration of total cholesterol (P = 0.03;OR:1.12;95%CI:1.01,1.23). In univariate analysis, an increasing degree of ECAS was significantly correlated with a thinner RNFL. Conclusions Higher prevalence and degree of ECAS were correlated with thinner RNFL and vice versa. Patients with abnormally thin RNFL without ocular disease may undergo carotid artery examination to detect asymptomatic carotid artery stenosis. Examination of the RNFL is useful for the diagnosis of cerebrovascular disease.